The Effect Of Entrepreneurial Orientation And Human Capital On Tapis Business Resilience With Social Capital As Moderating Variable - Cinthya Bella; Asep Mulyana; Yudi Ahmad Faisal (UNIVED Press, 2024)
The rise of Micro, Small, and Medium Enterprises (MSMEs) increases inevitable competitors and business fields that continuously change. The existence of competition makes the SMEs should face many opportunities and threats. The researcher would like to know more about how entrepreneurial orientation, human capital, and social capital could affect Tapis business resilience in Bandar Lampung. This research used the survey method, which is a type of quantitative approach. Respondents of this research are 119 tapis craftsmen in Bandar Lampung, the researcher will use Smart PLS 3.0 to process data. The result of this research shows that entrepreneurial orientation has a positive and significant effect on business resilience, human capital does not affect business resilience, social capital positively moderates the effect of entrepreneurial orientation on business resilience, and social capital does not moderate the effect of human capital on business resilience.